Síntese e caracterização de novos compostos envolvendo Índio e Calcogênios - Mello, Melina de Azevedo (2015)
This work is composed of two parts. The first one describes the synthesis of organometallic compounds derived from Br2InCH2Br and dichalcogenoether ligands, RE(CH2)nER (E = Se, Te; n = 1, 3; R = Ph, p-C6H4NMe2), compounds 1 to 6, that are considered chemical intermediates with potential application in organic synthesis; and the second part describes the preparation of a series of InIII-E-MI ternary clusters (E = S, Se; MI = Cu, Ag; compounds 7 11), which show potential applications as semiconductors or photocatalysts. In the first part, bimetallic compounds Br3InCH2E(R)(CH2)nE(R)CH2InBr3 were obtained where n = 3, E = Se, Te e R = Ph, p-C6H4NMe2 (compounds 1, 3 and 6). Where n = 1, the compounds obtained have only one InIII atom, Br3InCH2E(Ph)CH2EPh (compounds 2 and 4); and also the bimetallic compound Br3InCH2Te(Ph)CH2Te(Ph)CH2InBr3 (5) could be obtained. Compounds 1 6 were characterized by Nuclear Magnetic Resonance of the corresponding chalcogen, and by Mass Spectrometry. In the second part, the InIII-E-MI ternary clusters (E = S, Se, MI = Cu, Ag) were synthesized from indium(III) chalcogenolates: In(EPh)3 (compounds 7 10) or BrIn(p-SeC6H4NMe2)2 (compound 11). Compounds 7 to 11 were characterized by X-ray Diffraction, Infrared Spectroscopy, and had their optical band gaps evaluated, in the solid state, by Ultraviolet/Visible Spectroscopy. Finally, compound 9 was used as sensitizing agent of TiO2, and used as photocatalyst to obtain hydrogen by visible light induced water splitting. The sensitizing process of TiO2 with compound 9 improved considerably the H2 evolution when compared with the use of pure TiO2 in the studied conditions.